(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
To evaluate the relationships between clinical, morphological, and molecular factors— specifically the expression of EGFR and VEGF—and their association with regional metastasis in colorectal cancer, aiming to improve prognostic accuracy and guide personalized treatment strategies.